Multiple Rock Breakdown in Electrodischarge Technology; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Vazhov V. M. Vladislav; Datskevich S. Yu. Sergey Yurievich; Zhurkov M. Yu. Mikhail Yurievich; Muratov V. M. Vasily Mikhailovich; Rodland A. Arild (Electrophysical and Electrochemical Methods and Technologies of Materials Treatment, 2016)
Title screen